Supply chain finance and SMEs: Evidence from international factoring data - Marc Auboin; Harry Smythe; Robert Teh (World Trade Organization (WTO), 2016)
The unbundling of trade across regions offers unique opportunities for SMEs to integrate into global trade notably through their involvement into supply-chains. With supply-chains shifting and expanding into new regions of the world, the challenge for SMEs to accessing financing remains an important one; in many developing and emerging market economies, the capacity of the local financial sector to support new traders is limited. Moreover, after the financial crisis, several global banks have "retrenched", for various reasons. In this context, supply-chain finance arrangements, and other alternative forms of financing such as through factoring, have proven increasingly popular among traders. This paper shows that factoring has a positive effect in allowing SMEs to access international trade, in countries in which it is available. Factoring also appears to be employed by firms involved in global supply chains. We employ for the first time data on factoring from Factor Chain International (FCI), the most extensive dataset on factoring available at the moment, for the period of 2008-2015. Using an instrumentation strategy we identify a strong, stable effect of factoring on SMEs access to capital for some of the main traders in the world.
Keywords: F13; F34; G21; G23; 330; trade credit; financial crisis; trade